RESTORATION OF THE CONSTRUCTION AND ROAD MACHINES’ DETAILS FROM GREY CAST IRON: IMPROVEMENT OF THE REPAIR DIMENSIONS’ METHOD EFFICIENCY - V. E. Ovsyannikov; V. I. Vasilyev (Вестник СибАДИ)
Introduction. The total mass of some grey cast iron details in construction and road machines reaches 60%. Cylinder blocks, parts of braking systems, flywheels, etc. are made of cast-iron. One of the main causes of operational failures (up to 70%) of construction and road machines is failure of friction units. Considering that the contacting parts in these units take the load mainly by surface layers. The operability looses at relatively small values of dimensional wear. Although mass wear of the part usually does not exceed 1%.Materials and methods. The authors carried out a comprehensive technical and economic analysis of repair methods of friction assemblies. As a result, the best combination of criteria was the repair size method. However, the strengthened layer was removed to the repair dimension by conventional reconditioning technology. At the same time grey cast iron was strengthened only by very expensive and labor-intensive methods, which in conditions of real repair production were not applicable. The authors considered the possibility of using a new method of strengthening iron parts in repair works.Results. The developed method strengthened grey cast iron with layer thickness up to 3 mm. The distinctive feature was that hardness of the strengthened layer in thickness increased. At the same time the microhardness increased in comparison with the initial grey iron more than 2 times and wear resistance became comparable to high-strength hardened stun.Discussion and conclusions. The authors obtain the best results with the usage of reducing atmosphere furnaces. In order to expand the scope of the method, the researches proposed to use a special device creating the necessary conditions in any furnace. The application of the proposed technical solutions increases the efficiency of the construction and road machines’ repair.The authors have read and approved the final manuscript. Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.